2014
DOI: 10.1371/journal.pone.0090966
|View full text |Cite
|
Sign up to set email alerts
|

Variants of CEP68 Gene Are Associated with Acute Urticaria/Angioedema Induced by Multiple Non-Steroidal Anti-Inflammatory Drugs

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are the most consumed drugs worldwide because of their efficacy and utility in the treatment of pain and inflammatory diseases. However, they are also responsible for an important number of adverse effects including hypersensitivity reactions. The most important group of these reactions is triggered by non-immunological, pharmacological mechanisms catalogued under the denomination of cross-intolerance (CRI), with acute urticaria/angioedema induced by multiple NSAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Seventeen variants showed evidence of association with NIUA, including the SNP rs7572857. Moreover, 8 of these polymorphisms were also marginally associated with NERD and blended reactions [126]. Although our findings suggest a role for CEP68 in crosshypersensitivity to NSAIDs, the molecular basis for these associations requires further elucidation.…”
Section: Beyond the Candidate Gene Approachmentioning
confidence: 66%
See 1 more Smart Citation
“…Seventeen variants showed evidence of association with NIUA, including the SNP rs7572857. Moreover, 8 of these polymorphisms were also marginally associated with NERD and blended reactions [126]. Although our findings suggest a role for CEP68 in crosshypersensitivity to NSAIDs, the molecular basis for these associations requires further elucidation.…”
Section: Beyond the Candidate Gene Approachmentioning
confidence: 66%
“…The authors found an intriguing association between the decline in FEV 1 and a nonsynonymous polymorphism (rs7572857, Gly74Ser) in centrosomal protein of 68 Kd (CEP68) [123], a gene involved in centrosomal cohesion and epidermal growth factor signaling [124,125]. Our group evaluated 53 common SNPs in this gene in a population of Spanish patients presenting NIUA, NERD, and blended reactions [126]. Seventeen variants showed evidence of association with NIUA, including the SNP rs7572857.…”
Section: Beyond the Candidate Gene Approachmentioning
confidence: 99%
“…Seventeen SNPs, including the Gly74Ser variant, were associated with NIUA. Although not remaining significant after multiple testing corrections, 8 of these variants were also associated with NERD and blended reactions [83]. These results suggest that CEP68 variants may play a key role in the development of various manifestations of NSAIDinduced hypersensitivity.…”
Section: Gwas Approachmentioning
confidence: 79%
“…The most significant associations were found for SNPs in a 68-kDa centrosomal protein (CEP68), and the nonsynonymous polymorphism rs7572857 (Gly74Ser) was associated with the decline in FEV 1 [100]. We recently analyzed 53 common CEP68 variants in a Spanish population of patients with NSAID-induced DHRs including NIUA, NERD, and blended reactions [83]. Seventeen SNPs, including the Gly74Ser variant, were associated with NIUA.…”
Section: Gwas Approachmentioning
confidence: 99%
“…The MHC-encoded susceptibility genes Between 1999 and 2014, eight studies, mainly from Spain, evaluated potential genetic predictors in association with NAR to NSAIDs (43)(44)(45)(46)(47)(48)(49)(50). The first report by Quiralte et al evaluated .…”
Section: Genetic Predictors Of Nar: the Examples Of Nonspecific Reactmentioning
confidence: 99%